REKONSTRUKSI PEMIKIRAN HABERMAS DI ERA DIGITAL - Jaduk Gilang Pembayun (Universitas Tidar, 2017)
Public sphere is a theory who created and popularized by Habermas who focus on a historical studies of a critical discussion as a feedback to social realities consists of politic, culture, and anything else that interests the citizen happen in 18th century. Emergence of the internet as a new media make cultural change and transfrom the public sphere into something that has a big scale who can access anywhere and anytime. This is a point of the attention to see how shape, character and the problem about the public sphere in the digital era.